STRATEGI PEMERINTAH DESA DALAM PEMBERDAYAAN KELOMPOK TANI DI DESA SUNGAI SEGAK KECAMATAN SEPAUK KABUPATEN SINTANG - antonius, Antonius (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2024)
In this case, the village government is the spearhead of government, an acronym for the central government which, by mingling directly with the community, is expected to be effective in carrying out the government's duties as the government in the village in order to realize development in all fields. In this case, a village is a territorial unit inhabited by a number of families who have their own government system. Efforts to realize regional independence reflect the role of community participation in the development process which is based on policy rules to participate according to the proportion and competence they possess. In other words, empowering farmer groups is to enable and make the community independent in terms of welfare. Therefore, a strategy/way is needed to empower farmers to increase agricultural productivity. This research aims to find out about the implementation of village government strategies in empowering communities in Sungai Segak Village. This is based on the large number of people in Sungai Segak village who work as farmers and are supported by The geographical and topographic conditions of Sungai Segak village itself are suitable for use as an agricultural area. This research uses descriptive qualitative research methods. From the research results, it was found that the village government's strategy was not implemented well and was not working in place. There were several farmer groups in this village that were not empowered by the government. Apart from government factors, human resource capacity also had an influence on the development of farmer groups in Sungai Segak Village, Sepauk District.